Effectiveness of SHCC strips reinforced with glass fiber textile mesh layers for shear strengthening of RC beams: Experimental and numerical assessments. (11th April 2022) - Baraghith, Ahmed T.; Mansour, Walid; Behiry, Reda N.; Fayed, Sabry
Highlights: GFTM-SHCC strips were investigated for shear strengthening of RC beams. The effect of SHCC orientation, configurations, and continuity were examined. Thirteen RC beams under three-point loading have been experimentally tested. A shear capacity increase of 47–142% was achieved. A FE model agreed well with the experimental records. Abstract: In the present study, the potential of the use of strain-hardening cementitious composite strips internally reinforced with glass fiber textile mesh layers (GFTM-SHCC) as a strengthening system for shear-critical reinforced concrete (RC) beams is examined. For this purpose, thirteen simply supported beams incorporating two bare control specimens were tested under a three-point loading scheme. The GFTM-SHCC strips were applied inside 20 mm grooves within the beams' substrate so as to prevent the likelihood of premature debonding failure and to significantly enhance the utilization of the adopted strengthening system. The considered key parameters were the layers' number of the GFTM within the SHCC strip (2, 4, or 6), the spacing between GFTM-SHCC strips (90, 150, or 225 mm), the GFTM-SHCC orientation angle (45°, 60°, or 90°), and the strengthening configurations (side-bonded, U-wrapped, or fully-wrapped). Moreover, the location of the strengthening strips relative to the internal stirrups, if they exist, (aligned or un-aligned), was of interest. The effectiveness of GFTM-SHCC was evaluated in terms of failure patterns, ultimate shear capacity, and the gain in ductility. Experimental results revealed the effective implementation of the GFTM-SHCC strengthening strips in improving the ultimate shear capacity and the deformation characteristics of the tested specimens; however, their behavior relied on the test parameters. The shear carrying capacity and the ductility of the strengthened RC beams using GFTM-SHCC strips were in the range of 47–142% and 21–172%, respectively, higher than their counterpart control specimens. Furthermore, among all strengthening configurations, fully-wrapped strengthened RC beams demonstrated the highest gains in shear capacity, while inclined GFTM-SHCC strips with orientation angles of 45° and 60° outperformed vertical strips significantly. An analytical model to predict the ultimate shear capacity of the strengthened RC beams was derived and verified against the experimental results. To further assess the potential of the GFTM-SHCC strips for the shear strengthening of RC beams, a three-dimensional (3D) non-linear finite element model (FEM) was created using ABAQUS software and verified against the experimental records. After affirmation of the satisfactory predictive performance of the numerical model, a parametric study was performed to compare the shear responses of RC beams strengthened with intermittent GFTM-SHCC strips with continuous ones (strengthened along the whole shear span zone).